Raman spectroscopic investigations into links between intrinsic reactivity and char chemical structure - Wang, M.; Roberts, D.; Kochanek, M.; Harris, D.; Chang, L.; Li, Chun-Zhu (Curran Associates, Inc., 2013)
There are a large number of factors affecting the gasification reactivity of chars, including physical structure (e.g. surface area and pore structure), catalytically-active mineral matter, and chemical structure which includes the extent of crystallinity of the carbonaceous matrix and also the nature of the functional groups that comprise the char structure. This work focuses on the latter, using Raman spectroscopy to investigate the relationships between intrinsic reactivity and char chemical structure. An Australian bituminous coal char and a Chinese lignite char were characterised in terms of their intrinsic reactivities with CO2 and H2O (separately), under conditions where chemical processes control the observed reaction rates (Regime I). Unreacted and partially-reacted chars were characterised using Raman spectroscopy and gas adsorption for determination of chemical structure indicators and surface area respectively. Raman spectra suggested that the ratio of small to large aromatic rings decreased with increasing carbon conversion, and for the bituminous coal char, this seemed to be linked to the reactivity behaviour of chars made from the bituminous coal. The intrinsic reactivity of chars made from the lignite seemed to have a less significant correlation with Raman features, possibly due to the relative influence of catalytic activity of inorganic species.